E-Cybernetique: Etika Berinternet Dalam Bersosial Media Bagi Anak-Anak Sekolah Dasar Di Pekon Suka Maju Kecamatan Ngaras Kabupaten Pesisir Barat Provinsi Lampung - Putri, Intan; Mulyadi, Ahmad Iman; Adli; Dendi; Nanda Syukerti (LPPM UMRI, 2023)
The ethics of communicating on social media in using social media. The more technology develops, the more rapidly social media is in today's world, so that we can get to know media communication, namely in this study through social media. In using social media, of course you can't go around like that, but there are communication ethics that need to be considered, in using social media. The use of the internet is indeed very helpful and relieves solving problems in everyday life. There is a positive side and a negative side. Therefore, parents and teachers have a very important role in supervising and directing their children in using the internet. Children can choose positive internet content. Indeed, there must be collaboration in instilling knowledge about internet use by separating oneself from negative things. Currently the internet is very global in human life, especially in children. For them, the internet is really needed in completing many tasks, but it turns out that the internet also has negative effects on them. Moreover, elementary school age children who do not have mental maturity, are immature in acting and thinking, so they are easily swept up by the currents of globalization.